ANALYSIS OF TECHNICAL AND RESOURCE USE EFFICIENCY AMONG SMALLHOLDER YAM FARMERS IN TARABA STATE, NIGERIA - Abubakar, B.; Abubakar, A. A.; Ojeleye, O. A.; Owolabi, M. A.; Yusuf, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the technical and resource-use efficiency among smallholder yam farmers in Taraba State, Nigeria. Multistage sampling technique was used to select cross-sectional data from 244 smallholder yam farmers in Jalingo, Yorro and Zing local government areas of Taraba State, Nigeria. The stochastic frontier analysis (SFA) was used to analyse the driving factors of yam output and measure the technical efficiency level of farmers while the marginal value product– marginal factor cost (MVP-MFC) approach was used to estimate the efficiency of resource use in yam production. The study found out that the mean technical efficiency of the yam farmers was 76.31 %, which means that 23.69% of the technical output was not achieved. Moreover, the study also revealed that level of education and numbers of extension visit exert a positive and significant effect on the technical efficiency at 1 % level. Likewise the study shows that age, farming experience, years in cooperative membership and the amount of credit received were positive and significant at 5 % level while family size was positive and exert a significant effect on the technical efficiency at 10 %,. Finally, the result of the resource use efficiency showed that farm size (29.37), yam set/seed (1.52) and agrochemicals (1.15) were found to be under-utilized while fertilizer (0.047) and labour (0.08) was found to be over-utilized. In general, the study revealed that elasticity of production is greater than unity (2.221). It can be concluded that yam farmers in the study area were operating at increasing returns to scale. The study recommends that policies and strategies should place more emphasis on strengthening the existing agricultural extension service provision through providing incentives, short and long-term training, and upgrading educational level, providing non-overlapping and congruent responsibilities to extension workers. The study also recommended that to achieve optimum resource use efficiency and hence maximum profit in yam production in the study area, farmers should be encouraged to maximise the use of land, yam set/seed and agrochemical and minimize the use of labour and fertilizer respectively in order to improve the farmers’ productivity and income in the study area. This can be achieved through appropriate policy options that would encourage the reallocation and redistribution of these inputs.